PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI SUPERVISI DAN PENDAMPINGAN INTENSIF - FAIZIN FAIZIN (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2021)
Teacher competence is a statement of criteria in the form of mastery of a set of knowledge abilities, attitudes, values ??and skills for an educator. Teachers are expected to have competencies in accordance with the specified standards, namely: 1) learning management, 2) professional development, and 3) academic mastery. One of the successes of learning management is determined by the competence of the teacher in preparing the Learning Implementation Plan (RPP). The results of device supervision and academic supervision before the study showed that the competence of teachers, especially in preparing lesson plans was not in accordance with the criteria for preparing good lesson plans. This has a negative impact on the learning process and learning outcomes to be achieved. Schools as places for education and learning need to make efforts to improve teacher competence in learning planning. Efforts taken by researchers as school principals are to carry out continuous intensive supervision and assistance activities. Therefore, researchers carry out School Action Research (PTS) which aims to determine the increase in teacher competence in preparing lesson plans through supervision and intensive mentoring. PTS was carried out in two cycles. The flow of each cycle includes: action planning, implementation, observation, analysis of results and reflection. The initial conditions of the study based on device supervision showed that the average value of conformity with the correct RPP components was 52%. The results of the teacher's competence in preparing lesson plans after the research was carried out in Cycle I obtained an average value of conformity with the RPP components of 69%. In Cycle II, the average value of conformity with the RPP components increased to 83%. The results of the academic supervision of Cycle I obtained the percentage of achievement of 56% and Cycle II increased to 85%. Thus, intensive supervision and mentoring can improve the competence of teachers in preparing lesson plans. ABSTRAKKompetensi guru merupakan suatu pernyataan tentang kriteria dalam bentuk pengusaan seperangkat kemampuan pengetahuan, sikap, nilai dan keterampilan bagi seorang Pendidik. Guru diharapkan memiliki kompetensi sesuai dengan Standart yang ditentukan yaitu: 1) pengelolaan pembelajaran, 2) pengembangan profesi, dan 3) penguasaan akademik. Keberhasilan pengelolaan pembelajaran salah satunya ditentukan oleh kompentensi guru dalam menyusun Rencana Pelaksanaan Pembelajaran (RPP). Hasil supervisi perangkat maupun supervisi akademik sebelum penelitian menunjukkan bahwa kompetensi Guru, terutama dalam menyusun RPP belum sesuai dengan kriteria penyusunan RPP yang baik. Hal ini berdampak negatif pada proses pembelajaran dan hasil belajar yang akan dicapai. Sekolah sebagai tempat penyelenggaraan pendidikan dan pembelajaran perlu melakukan upaya untuk meningkatkan kompetensi Guru dalam perencanaan pembelajaran. Upaya yang ditempuh Peneliti sebagai kepala sekolah adalah melaksanakan kegiatan supervisi dan pendampingan intensif secara kontinu. Oleh karena itu Peneliti melaksanakan Penelitian Tindakan Sekolah (PTS) yang bertujuan untuk mengetahui peningkatan kompetensi guru dalam menyususun RPP melalui supervisi dan pendampingan intensif. PTS dilaksanakan sebanyak dua siklus. Alur setiap siklus meliputi: perencaan tindakan, pelaksanaan, pengamatan, analisa hasil dan refleksi. Kondisi awal penelitian berdasarkan supervisi perangkat menunjukkan bahwa nilai rata-rata kesesuaian dengan komponen RPP yang benar sebesar 52%. Hasil kompetensi Guru dalam menyusun RPP setelah penelitian dilaksanakan pada Siklus I diperoleh nilai rata-rata kesesuaian dengan komponen RPP sebesar 69%. Pada Siklus II nilai rata-rata kesesuaian dengan komponen RPP meningkat menjadi 83%. Hasil Supervisi akademis Siklus I diperoleh prosentase ketercapaian sebesar 56% dan Siklus II meningkat menjadi 85%. Dengan demikian supervisi dan pendampingan intensif dapat meningkatkan kompetensi Guru dalam menyusun Rencana Pelaksanaan Pembelajaran.